TINGKAT KEPUASAN NASABAH TABUNGAN TERHADAP PELAYANAN BANK : STUDI KASUS DUA BANK DI BANDAR JAYA KECAMATAN TERBANGGI BESAR KABUPATEN LAMPUNG TENGAH - Mustika, Tika; Hudoyo, Agus; Kasymir, Eka (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
The economic growth in the Central Lampung district has been increasing the demand of financial service. It has been affecting the growth of banks. Furthermore among banks has been competing to obtain and retain their customers. To do so, a bank has to fulfill the expectation of its customers. The main objective of this research is to investigate the performance of bank in fulfilling the expectation of its customers. Two banks in Bandar Jaya of Central Lampung district were choosen. From each bank, 30 respondents were interviewed by using questioners. Data were analyzed using the Importance Performance Analysis (IPA). The results showed that Bank A dan Bank B were under performed based on customers expectation in this two atributes, i.e. the speed of giving service and the response to new customers. In Bank A, the atribute of response to customers using telephone was under performed. Key words : service, performance, Importance Performance Analysis (IPA), bank, customers satisfaction